2018
DOI: 10.1097/iae.0000000000001708
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar Hole-Associated Epiretinal Proliferation in Lamellar Macular Hole and Full-Thickness Macular Hole in High Myopia

Abstract: Lamellar hole-associated epiretinal proliferation in HM tended to be more widespread and adherent to the posterior hyaloid than in eyes without HM. Visual outcomes after LMH repair in eyes with LHEP and HM are less favorable than eyes with LHEP and without HM, but similar to eyes with HM and without LHEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 16 publications
5
36
0
1
Order By: Relevance
“…Besides, previous studies also indicated that LMH or FTMH eyes with LHEP had worse visual outcomes after surgery [8,13,14,24], probably attributable to the severer destruction of the retina in eyes with LHEP than without LHEP. However, there are also some studies reported similar surgery outcomes of eyes with and without LHEP [10,12,15,16]. As there are no signi cant differences in preoperative BCVA (<20/40), surgery method (ILM and ERM peeling) and time of follow-up (>6 months) among these two kinds of studies, more studies with longer follow-up are required to determine the relationship between the poor visual outcomes and LHEP.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Besides, previous studies also indicated that LMH or FTMH eyes with LHEP had worse visual outcomes after surgery [8,13,14,24], probably attributable to the severer destruction of the retina in eyes with LHEP than without LHEP. However, there are also some studies reported similar surgery outcomes of eyes with and without LHEP [10,12,15,16]. As there are no signi cant differences in preoperative BCVA (<20/40), surgery method (ILM and ERM peeling) and time of follow-up (>6 months) among these two kinds of studies, more studies with longer follow-up are required to determine the relationship between the poor visual outcomes and LHEP.…”
Section: Discussionmentioning
confidence: 98%
“…By reading the titles and abstracts, 14 papers on LHEP reporting surgical outcomes were identi ed. Then, the full texts of all articles were read and 6 of them were discarded because they included patients with FTMH [8,9], recruited LMH patients with high myopia [10], had incomplete information [11,12] or was an observational study without surgery [3]. Finally, eight studies with 176 eyes without LHEP and 173 eyes with LHEP were included [13][14][15][16][17][18][19][20].…”
Section: Characteristics Of the Available Studiesmentioning
confidence: 99%
“…LMH is idiopathic in most cases, but it may be secondary to: cystoid macular edema due to metabolic or vascular retinal diseases [25-29], retinochoroiditis [30], age-related macular degeneration [31], retinitis pigmentosa [32], X-linked retinoschisis [33], myotonic dystrophy [34], Alport syndrome [35], Coats’ disease [36], high myopia [10, 37-40], ocular trauma [41, 42], or iatrogenic damage during intravitreal injection or surgery [43-48]. …”
Section: Pathogenesismentioning
confidence: 99%
“…Опираясь на данные собственных наблюдений, T.T. Lai et al (2016Lai et al ( , 2018 пришли к выводу, что результаты хирургического лечения на глазах с LHEP и без неё идентичны, несмотря на больший процент повреждения эллипсоидной зоны в первом случае [51], а результаты хирургического лечения несквозных и сквозных макулярных разрывов с LHEP при высокой миопии не настолько благоприятны, как при эмметропии [52].…”
Section: результаты хирургического лечения и их прогнозированиеunclassified